Pengaruh Model Pembelajaran Kooperatif Tipe Kancing Gemirincing terhadap Hasil Belajar Siswa pada Materi Termokimia - Ernika Novianda; Sri Lestari; Yuli Hartati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The Jingling Button Type Cooperative Learning Model is a learning model whose main objective is to achieve equal learning opportunities for each student so that students become more active in the learning process. This research aims to determine the effect of the rattling button type cooperative learning model on student learning outcomes in thermochemical material at SMA Negeri 2 Tenggarong Seberang. The research population was all students of class XI MIPA SMA Negeri 2 Tenggarong Seberang. Sampling used a cluster random sampling technique, so that the research samples were obtained, namely class XI MIPA 2 students and class XI MIPA 3 students. Student learning outcomes were obtained from posttest scores and daily tests. The data analysis techniques used are normality test, homogeneity test and t test. The results of the analysis of the data obtained show that the average learning outcome score for experimental class students is 82.65, which is higher than the average learning outcome score for control class students, which is 72.62. Based on the results of the data analysis that has been carried out, it can be concluded that the application of the rattling button type cooperative learning model has a better influence on student learning outcomes at SMA Negeri 2 Tenggarong Seberang on Thermochemistry material.